Consumo e cidadania : o perfil e a experiência dos usuários do Procon/Sergipe - Freire, Mário José Correia (2009)
This work has as objective to analyze the profile and the experience of the users of the public politic performed by the Coordenadoria Estadual de Proteção e Defesa do Consumidor (Procon/SE), focusing the perception of the users concerning its effectedeness as a facilitator for the full exercise of citizenship through the assurance of the accomplishment of the norms present in the Código de Defesa do Consumidor, that is its institutional mission. In order to achieve this goal, one decided to apply a qualitative approach combined with some aspects of the quantitative approach in terms of methodology this one particularly used to identify the profile of the peoples surveyed. The theoretical reference includes a description and a conceptual analysis concerning the thematic of citizenship, conceived as fundamental precept of individual existence and means of extension of equality in modern world, based on three dimensions of rights: civil, politic and social (Marshal); State, civil society and market with their respective distinctions constructed historically, finally emphasizing the peculiarities of the Brazilian experience; with its contradictions and weaknesses, and its distinction in relation to other countries (Carvalho). Concerning the relationship between consumption and citizenship one analyzed the so called culture of consumption in the context of post-modern society, in which the sign is the goods instead of the value of using (Baudrillard); consumercitizen in his cultural processes and practices, by selecting and by appropriating goods (public or private), follows a definition of what he considers socially valuable, like condition for integration and social difference wanted (Canclini); and the phenomenon of consumerism, that makes the act of consuming central in people s lives, like real purpose of existence (Bauman). The results revealed the predominance of young users in intermediate level of formal education and relatively low familiar income, without participation in social organizations of collective character. These results also revealed that the main elementworking as a channel of advising of the services of Procon/SE for its users was the television,the same means which paradoxically encourages them to consume more and more in aconstant and intense way, applying analyzing the perception of the users surveyed referring to Procon/SE, one verified some effectiveness of this bureau as instrument to provide the contemplation of some demands andexpectations of consumers, confirmed by high indices of satisfaction and return. However, itwas possible to conclude that the public politic of defense and protection of consumerpresents limitations in its role of former of citizens, especially by lack of knowledge of theirusers concerning the limits and possibilities of the institutional action of that publicorganization.